PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DAN KOMPENSASI SEBAGAI VARIABEL INTERVENING PADA PT CEMINDO GEMILANG - Putra Glorius Putra Manurung (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
The research aims to effect of leadership and job environment toward employee performance and compensation as an variable intervening at PT Cemindo Gemilang. The numbers of samples are 63 respondents. The validity test of sample with loading factor test and the average variance extracted (AVE) value, while the reliability used cronbach’s alpha and composite reliability test based and the value. The loading factor test and the value of the average variance extracted (AVE) showed valid values. The internal consistency test had composite reliability value which meet the criteria. Based and rhe test result, all indicator variable statements have met the criteria of validity and reliability. The hypothesis test with SmartPLS 3.0 show leadership had not significant towards employee performance, job environment had positif effect and significant towards employee performance, compensation had not significant towards employee performance, leadership had not significant towards compensation, job environment had positif effect and significant towards compensation, performance leadership had not significant towards employee performance through compensation, and job environment had not significant towards employee performance through compensation.